Biomolecular Composition and Revenue Explained by Interactions between Extrinsic Factors and Endogenous Rhythms of Saccharina latissima - Xueqian Zhang; Marianne Thomsen (Marine Drugs, 2019)
This review provides a systematic overview of the spatial and temporal variations in the content of biomolecular constituents of Saccharina latissima on the basis of 34 currently available scientific studies containing primary measurements. We demonstrate the potential revenue of seaweed production and biorefinery systems by compiling a product portfolio of high-value extract products. An investigation into the endogenous rhythms and extrinsic factors that impact the biomolecular composition of S. latissima is presented, and key performance factors for optimizing seaweed production are identified. Besides the provisioning ecosystem service, we highlight the contribution of green-engineered seaweed production systems to the mitigation of the ongoing and historical anthropogenic disturbances of the climate balance and nutrient flows. We conclude that there are risks of mismanagement, and we stress the importance and necessity of creating an adaptive ecosystem-based management framework within a triple-helix partnership for balancing the utilization of ecosystem services and long-term resilience of aquatic environment.